2016
DOI: 10.1080/02673843.2016.1227716
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and Problematic Internet Use: a systematic review of longitudinal research trends in adolescence and emergent adulthood

Abstract: The aim of this systematic literature review is to map the longitudinal research in the field of Internet Use (IU) and Problematic Internet Use (PIU) in adolescents and emergent adults. Further, this study endeavours to examine the terminology and instruments utilized in longitudinal IU and PIU research and investigate whether statistically significant results have arisen from the areas of research focus. In a total of 29 studies, trends in the research of adolescent/emergent adult IU and PIU were discovered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
415
1
48

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 549 publications
(525 citation statements)
references
References 55 publications
27
415
1
48
Order By: Relevance
“…At this point it it should be noted that in line with the above, the international literature has consistently conceptualized flow as a precursor of IA behaviors and not the opposite (Anderson et al, 2016;Stavropoulos et al, 2013;Douglas et al, 2008;Kim & Davis, 2009;Rettie, 2001). Particulalry, it has been postulated that the experience of online "flow", as an emotional state, defines the quality/intensity (e.g., absorbance, length of time and the level of disconnection from the offline world) of Internet use, and therefore, the potential emergence of IA behaviors (e.g., it is the level of flow experience that may result to IA and not the other way around; Anderson et al, 2016;Stavropoulos et al, 2013;Douglas et al, 2008;Kim & Davis, 2009;Rettie, 2001).…”
Section: Online Flowmentioning
confidence: 58%
See 4 more Smart Citations
“…At this point it it should be noted that in line with the above, the international literature has consistently conceptualized flow as a precursor of IA behaviors and not the opposite (Anderson et al, 2016;Stavropoulos et al, 2013;Douglas et al, 2008;Kim & Davis, 2009;Rettie, 2001). Particulalry, it has been postulated that the experience of online "flow", as an emotional state, defines the quality/intensity (e.g., absorbance, length of time and the level of disconnection from the offline world) of Internet use, and therefore, the potential emergence of IA behaviors (e.g., it is the level of flow experience that may result to IA and not the other way around; Anderson et al, 2016;Stavropoulos et al, 2013;Douglas et al, 2008;Kim & Davis, 2009;Rettie, 2001).…”
Section: Online Flowmentioning
confidence: 58%
“…More specifically, longitudinal findings have shown that males are more inclined to develop problems with impulse-control and sensation-seeking behaviors than females, and these symptoms have been associated with IA (Kuss et al, 2014;Shulman, Harden, Chein, & Steinberg, 2015). Additionally, cross-sectional studies of Internet use have indicated adolescent males being at higher risk of IA than adolescent females (Shi, Wang, & Zou, 2017;Karacic & Oreskovic, 2017;Ostovar et al, 2016;Anderson et al, 2016;Chen et al, 2015;Choo et al, 2015;Gentile et al, 2011;Haagsma et al, 2013;Hong et al, 2014;Willoughby, 2008;Yu & Shek, 2013;Stavropoulos et al, 2013a;Yen et al, 2009;Shaw & Black, 2008;Johansson & Götestam, 2004). Higher digital skills and preference for more addictive applications (such as gaming) have been suggested to explain these findings (Kuss & Griffiths, 2012).…”
Section: Gendermentioning
confidence: 99%
See 3 more Smart Citations